THE NATURAL FOOD AND FEEDING HABITS OF TANK GOBY GLOSSOGOBIUS GIURIS HAMILTON DISTRIBUTED IN THE DOWNSTREAM SECTION OF THE TAM QUAN RIVER - Van Chi Vo; Kim Khue Ngo; Dieu Vo (Tạp chí Khoa học Đại học Đà Lạt, 2025)
Glossogobius giuris plays a vital role in the local food supply in the Tam Quan region of Binh Dinh Province, Vietnam. However, knowledge on its natural food composition and feeding habits in this area is very rare. Therefore, this study was conducted to fill this research gap. A total of 193 specimens were collected for study from January to June 2022 in the downstream section of the Tam Quan River. The relative length of the gut, the frequency of occurrence, the number percentage, the weight percentage, and the relative importance percentage of food items were examined. The results showed that the relative length of the gut varied from 0.68 to 0.72, indicating carnivorous feeding. The natural food composition was dominated by Acetes, followed by small fish and a small amount of Lucifer, showing that Glossogobius giuris is carnivorous. A feeding shift between three size classes, with changes in the ratio of food items, was found. The findings provide critical knowledge that may be used in aquaculture and in the conservation of this species.